2008
DOI: 10.1038/onc.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced translocation, a major chromosome alteration causing loss of heterozygosity in human lung cancer

Abstract: Loss of heterozygosity (LOH) is a major genetic event causing inactivation of tumor suppressor genes in human carcinogenesis. To elucidate chromosomal mechanisms causing LOH, 201 LOHs in 10 cases of human lung cancer, which were detected by a genome-wide single nucleotide polymorphism array analysis, were investigated for responsible chromosome alterations by integrating information on breakpoints for DNA copy number changes obtained by array-comparative genome hybridization and on numerical and structural chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…Thus, AI regions were defined by the criterion of containing at least six consecutive AI loci. Under the same criterion and by combination of SNP array data with spectral karyotyping and arraycomparative genomic hybridization data, 1 of 13 (7.7%) trisomic chromosomes was judged as AI, and 14 of 215 (6.5%) AI regions were due to amplification/gain of one allele in our recent study (22). Therefore, one of allelic chromosomal segments was likely to be lost in most (>90%) of AI regions defined in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, AI regions were defined by the criterion of containing at least six consecutive AI loci. Under the same criterion and by combination of SNP array data with spectral karyotyping and arraycomparative genomic hybridization data, 1 of 13 (7.7%) trisomic chromosomes was judged as AI, and 14 of 215 (6.5%) AI regions were due to amplification/gain of one allele in our recent study (22). Therefore, one of allelic chromosomal segments was likely to be lost in most (>90%) of AI regions defined in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The development of high-density SNP genotyping technology for genomic profiling represents a further advance, because simultaneous measurement of both signal intensity variations and changes in allelic composition makes it possible to detect both copy number changes and copy-neutral LOH events (30). This is particularly important, because copy-neutral LOH is receiving greater attention as a mechanism of possible tumor initiation (4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that acquired UPD is frequently encountered in hematologic malignancies (4)(5)(6)(7). In some studies, acquired UPD has also been observed in solid tumors (8)(9)(10), indicating that UPD can occur not only in familial diseases but also in acquired sporadic tumors. However, our knowledge about acquired UPD regions in sporadic tumors is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…LOH is the result of genetic and/or environmental variations through genomic instabilities including mitotic nondisjunction and recombination, chromosomal loss, DNA deletion and mutation, gene conversion and translocation [Cavenee et al, 1983;Ogiwara et al, 2008;Yokota et al, 1987]. LOH has been recognized as one of the most frequent chromosomal aberrations in the human genome.…”
Section: Introductionmentioning
confidence: 99%